Fluorescent spectroscopy of collagen as a diagnostic tool in medicine - Saletnik, Łukasz; Wesołowski , Roland (Journal of Medical Science, 2022)
Medicine continuously needs to improve the existing diagnostic solutions or introduce new ones. Despite the fact that collagen is a well described protein, collagen-related diseases represent the disorders requiring improvement particularly in terms of research tools. These diseases include connective tissue diseases, keratoconus, where a change in the structure of collagen is observed causing a deformation of the cornea, as well as neoplasms, in which the amount of collagen is multiplied in cells.Fluorescence spectroscopy constitutes a highly sensitive, non-invasive research method, thus, its use in medicine can contribute to the development of excellent diagnostic methods. This method allows to determine the changing amount of the tested fluorophores, as well as the change of the pH of the environment in which these fluorophores are located. Until now, numerous studies on collagen have been performed using fluorescence spectroscopy. However, a detailed analysis of the literature revealed some discrepancies which have been summarized in this paper.The collected experimental results allowed to conclude that the discrepancies in the obtained fluorescence excitation and emission spectra of collagen may result from the structural richness of collagen. Another reason for the variability of the results is the different experimental conditions, i.e. the excitation and detection of collagen fluorescence at different wavelengths. Therefore, it should be emphasized that collagen spectroscopy constitutes an extremely promising method, although the determination of the exact conditions of the experiment and their standardization are required in the research on the diagnostic use of this technique.
Keywords: collagen; cross-links; excitation spectra; emission spectra; fluorescence spectroscopy